Deficit to Asset Thinking: An Exploration of Incorporating Community Cultural Wealth on Preservice Teachers’ Mindsets - Howard, Amber K.; Bolyard, Chloe S.; Finley, Stacie L. (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2024)
This qualitative inquiry examined how using Yosso’s community cultural wealth (2005) model as a framework in a 16-week teacher-education course focused on home, schools, and communities which supported the development of 24 preservice teachers’ equity mindsets in relation to these spaces. To examine the nature of preservice teachers’ viewpoints, the following data sources were collected: a researcher-developed survey with open-ended questions based on Yosso’s model used as a pre- and post- survey, reflection assignments, and semi-structured interviews. These data were analyzed using priori coding based on the Equity Mindset Framework (Nadelson et al., 2019). Analysis revealed that Yosso’s community cultural wealth model provided a framework for preservice teachers to develop all eight attributes of an equity mindset to some degree, but three of those attributes were developed at a higher level: development of culturally relevant practices and thinking, the importance of understanding and knowing student populations, and taking responsibility for student success. This research has implications for teacher educators, as it provides guidance for a practical way to enhance preservice teachers’ equity mindset.